Inductive modeling site measurements in the process for environment - Квасніков, В.П.; Голуб, С.В. (Proceedings of National Aviation University (archive), 2006)
In work results of researches of multilevel systems of monitoring of an environment are submitted on the basis of inductive methods of modeling. For the decision of a problem of the coordination of models of different levels it is offered to use uniform technology of modeling. Results of application of a method of the group account of arguments for modeling objects voltamperometrik measurements of concentration of heavy metals in water on микро a level of monitoring of an environment, for modeling decease of the population of the Cherkassy area on Macro a level and for modeling results of administrative actions on Meta a level are submitted. Efficiency of the offered approaches and an opportunity of their use for monitoring medical and social and economic objects is shown.